LEGAL PROTECTION OF PERSONAL DATA OF SHOPEEPAY LATER LOAN USERS - Ramdani, Fahmi Ali; Amalina, Dini (Ilmu Hukum, Sharia and Law Faculty, Sunan Gunung Djati Islamic State University of Bandung, 2024)
Shopee Pay Later, which is a credit facility, is also a type of Fintech or Financial Technology with the term Fintech lending or also called Fintech Peer-to-Peer Lending, which is a payment method with an online lending system without having a bank account. By using the empirical legal research method, the researcher found cases related to the lack of consumer protection for Shopee Pay Later application users, namely Fitri Yeni Prihandono's sister with the occurrence of her account being hacked. This act violates Article 30 Paragraph 3 jo. Article 46 Paragraph 3 of Law Number 11 the Year 2008 jo. Law Number 19 of 2016 concerning Information and Electronic Transactions. In its development, Shopee has an obligation to its consumers in terms of consumer protection according to the provisions in Article 4 jo. Article 62 of Law no. 8 of 1999 concerning Consumer Protection. Shopee violates the security of the network which is already in the provisions of POJK No. 77/POJK.01/2016 concerning Information and Technology-Based Lending and Borrowing Services which is the basis for the regulation of the Pay Later system.Shopee Pay Later yang merupakan fasilitas kredit juga merupakan salah satu jenis Fintech atau Financial Technology dengan istilah Fintech lending atau disebut juga dengan Fintech Peer-to-Peer Lending, yang merupakan metode pembayaran dengan sistem peminjaman secara online tanpa harus memiliki rekening bank. Dengan menggunakan metode penelitian hukum empiris, peneliti menemukan kasus terkait kurangnya perlindungan konsumen terhadap pengguna aplikasi Shopee Pay Later yaitu saudari Fitri Yeni Prihandono dengan terjadinya peretasan akunnya. Perbuatan tersebut melanggar Pasal 30 Ayat 3 jo. Pasal 46 Ayat 3 Undang-Undang Nomor 11 Tahun 2008 jo. Undang-Undang Nomor 19 Tahun 2016 tentang Informasi dan Transaksi Elektronik. Dalam perkembangannya, Shopee memiliki kewajiban terhadap konsumennya dalam hal perlindungan konsumen sesuai ketentuan dalam Pasal 4 jo. Pasal 62 Undang-Undang No. 8 Tahun 1999 tentang Perlindungan Konsumen. Shopee melanggar keamanan jaringan yang sudah ada dalam ketentuan POJK No. 77/POJK.01/2016 tentang Layanan Pinjam Meminjam Uang Berbasis Teknologi Informasi dan Teknologi yang menjadi dasar pengaturan sistem Pay Later.